The Impact of Vertical Integration Intensity on Broiler Farms Technical Efficiency: The Case of Contract Farming in West Sumatera - Harianto Harianto; N. Kusnadi; D. A. Paramita (Faculty of Animal Science, Bogor Agricultural University, 2019)
Contractual arrangements of different types have increasingly found in West Sumatera not only in subsistence and commercial crops but particularly also in livestock sector. Contract farming in livestock agribusiness is generally defined as broiler farms under an agreement between farmers and a livestock inputs supplier. Within this broad definition, there are different variants of contracts depending on the formality and intensity of contractual arrangement. This study objective was to prove that the design of a contract, as representation of vertical integration intensity in broiler agribusiness, has different efficiency effects on production. The stochastic frontier production function was used in this study, and employed a regression method to estimate the level of technical efficiency. Data were collected from 87 broiler fattening farms consisted of 50 broiler fattening farms under formal contractual system and 37 broiler fattening farms under informal contractual system. The results showed that farm experience and improvement of the contract system would reduce the level of technical inefficiency of broiler farms. The study concluded that broiler farms under formal and detail contract farming had greater technical efficiencies compared to broiler farms under informal unwritten contract arrangement. However, the broiler farms under informal contract obtained higher net returns compared to the broiler farms under formal contract arrangement.